ANALISIS PERBEDAAN KEMAMPUAN LITERASI MATEMATIKA MODEL PISA SISWA SMP PADA KONTEN SPACE AND SHAPE DITINJAU DARI GENDER - Rahmayani, T. Yulia; Ellinawati; Ani Rusilowati; Multazam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the differences in mathematical literacy skills based onthe PISA model among junior high school students in the Space and Shape contentarea in terms of gender. The research employed a quantitative comparativeapproach with an ex-post facto design. The subjects consisted of 29 eighth-gradestudents from SMP Negeri 1 Bilah Barat, comprising 16 male and 13 femalestudents. The research instrument was a set of five mathematical literacy test itemsbased on the PISA model focusing on Space and Shape. Data analysis began witha normality test using Shapiro-Wilk and a homogeneity of variance test usingLevene’s Test. The results showed that the data for female students were notnormally distributed (Sig. = 0.002), while the data for male students were normallydistributed (Sig. = 0.054), and both groups had homogeneous variances (Sig. =0.710). Therefore, the non-parametric Mann-Whitney U test was used to test thehypothesis. The result showed a significance value of 0.180 (p > 0.05), indicatingthat there is no significant difference in mathematical literacy skills between maleand female students in the Space and Shape content based on the PISA model.These findings suggest that gender is not a significant factor in differentiatingstudents' mathematical literacy abilities in this context.